The invasion of the land - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Naturalist David Attenborough explains how marine vertebrates developed legs and lungs and were thus able to move onto the land. He also describes modern day amphibians, such as the salamanders and frogs.
Keywords: Vertebrates -- Evolution; Marine fauna -- Evolution; Amphibians -- Evolution